Metallic WO2-Promoted CoWO4/WO2 Heterojunction with Intercalation-Mediated Catalysis for Lithium–Sulfur Batteries - Wang, Chan; Zhang, Pengfei; Li, Jiatong; Wang, Rui; Yang, Changheng; Yu, Fushuai; Zhao, Xuening; Zhao, Kaichen; Zheng, Xiaoyan; Zhang, Huigang; Yang, Tao (Nano-Micro Letters, 2025)
Lithium–sulfur (Li–S) batteries require efficient catalysts to accelerate polysulfide conversion and mitigate the shuttle effect. However, the rational design of catalysts remains challenging due to the lack of a systematic strategy that rationally optimizes electronic structures and mesoscale transport properties. In this work, we propose an autogenously transformed CoWO4/WO2 heterojunction catalyst, integrating a strong polysulfide-adsorbing intercalation catalyst with a metallic-phase promoter for enhanced activity. CoWO4 effectively captures polysulfides, while the CoWO4/WO2 interface facilitates their S–S bond activation on heterogenous catalytic sites. Benefiting from its directional intercalation channels, CoWO4 not only serves as a dynamic Li-ion reservoir but also provides continuous and direct pathways for rapid Li-ion transport. Such synergistic interactions across the heterojunction interfaces enhance the catalytic activity of the composite. As a result, the CoWO4/WO2 heterostructure demonstrates significantly enhanced catalytic performance, delivering a high capacity of 1262 mAh g−1 at 0.1 C. Furthermore, its rate capability and high sulfur loading performance are markedly improved, surpassing the limitations of its single-component counterparts. This study provides new insights into the catalytic mechanisms governing Li–S chemistry and offers a promising strategy for the rational design of high-performance Li–S battery catalysts. Highlights: 1 The CoWO4/WO2 heterojunction was successfully constructed through hydrothermal synthesis of precursors followed by autogenous transformation induced by hydrogen reduction. 2 The synergistic effect of CoWO4 and WO2 promotes the catalytic conversion of polysulfides and suppresses the shuttle effect. 3 The CoWO4/WO2 heterojunction demonstrates significantly enhanced catalytic performance, delivering a high capacity of 1262 mAh g−1 at 0.1 C.